Options futures and other derivatives - Hull, John C.; Basu, Sankarshan (Delhi : Pearson, 2018)
Since the first edition of this book was published in 1988, there have been many developments in the options and the derivatives markets. The 10th edition of Options, Futures and Other Derivatives has taken into account these fast-paced changes and presents the reader with an up-to- date scenario. Like earlier editions, this book has been designed to serve the wider spectrum of the market. It is appropriate for students pursuing graduate courses in business, economics and financial engineering. It can be used for advanced undergraduate courses involving quantitative skills. Many practitioners who are involved in derivatives markets may also find the book useful.
Keywords: Options; Futures; Derivatives